Application of pulsed light treatment on quality retention and shelf life extension of fresh-cut yardlong bean - Hambali, Nor Hasni (2016)
Fresh-cut or minimally processed vegetables are in high demand as it is convenient and have fresh-like quality. However, fresh-cut processing promotes faster physiological deterioration, biochemical changes and microbial degradation which may affect the quality of fresh-cut vegetables. In this study, the effect of pulsed light fluences on microbiological stability and quality changes of selected dimension of fresh-cut yardlong bean were investigated. Selected combined ascorbic acid (ASA) or calcium chloride (CaCl2) dipping treatment with pulsed light treatment formulation for quality retention and shelf life extension of fresh-cut yardlong bean were also optimised using RSM. In addition, the effect of pulsed light combined with dipping treatment on quality (microbiological stability, respiration rate, physicochemical and sensory properties) and shelf life of fresh-cut yardlong bean were evaluated. Pulsed light treatments were carried out using an automatic laboratory flash lamp system (Steribeam XeMaticA-2L Kehl, Germany) at four different fluencies (1.8 J/cm2, 5.4 J/cm2, 9.0 J/cm2 and 12.6 J/cm2). Microbiological and shelf life quality (color, headspace gas composition and textural changes) of fresh-cut yardlong beans stored at 4±1°C were monitored over 16 days. Among these fluencies, 9.0 J/cm2 showed the most significant (p<0.05) effect in reducing total aerobic, yeast and mold counts but slightly affect the firmness and color of fresh-cut yardlong bean. Response surface methodology was employed to optimise the most effective formulation (concentration and dipping time) of ASA or CaCl2 combined with pulsed light treatment. The effect of pulsed light treatment combined with ASA or CaCl2 dip on the storage quality and shelf life of fresh-cut yardlong bean stored at 4±1°C for 20 days were evaluated. The optimum condition for dipping and pulsed light treatment is (0.1% (w/v), 1 min) for ASA and (0.1% (w/v), 1 min) for CaCl2. This combined treatment significantly (p<0.05) reduced the total aerobic, while maintained its sensory quality. Untreated sample reached the limit log 7 CFU/g (total aerobic counts) and log 5 CFU/g (yeast and mold counts) after 7 days of storage at 4±1°C while combined treatments extended the microbial shelf life up to 18 days. The morphology of the cell walls of fresh-cut yardlong bean treated with pulsed light combined with ASA or CaCl2 were similar to that of fresh yardlong bean while cell wall and tissue disruption were observed in control (untreated sample). It can be concluded that the combined treatment of pulsed light (9 J/cm2) with CaCl2 (0.1% w/v, 1 min) have potential to extend the shelf life up to 18 days while maintain the sensory quality of the fresh-cut yardlong bean compared to pulsed light alone which less than 14 days.